2009
DOI: 10.1007/s10811-009-9438-5
|View full text |Cite
|
Sign up to set email alerts
|

Monthly changes in the content and monosaccharide composition of fucoidan from Undaria pinnatifida (Laminariales, Phaeophyta)

Abstract: Crude fucoidan was extracted from the brown alga Undaria pinnatifida collected monthly from April to last July in Peter the Great Bay (Japan Sea, Russia). The amount of crude fucoidan rose markedly from April to June-July (from 3.2 to 16.0% dry weight) as the plant matures. An analysis of the monosaccharide composition of the fucoidan extracted showed that the alga synthesized polysaccharides with various structures which were dependent on the algae age. In juvenile plants collected in AprilMay, this was repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
81
1
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 33 publications
(53 reference statements)
6
81
1
9
Order By: Relevance
“…The authors also reported a correlation between fucoidan yield and seasonality; and more fucoidan was obtained during the reproductive stages of the seaweed. The physical and chemical states of the seaweed change during the reproductive stage [16] . In the present study, Sargassum during maturation period (September and October) gave highest yield of fucoidan and P. tetrastromatica collected during January, recorded higher yield.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors also reported a correlation between fucoidan yield and seasonality; and more fucoidan was obtained during the reproductive stages of the seaweed. The physical and chemical states of the seaweed change during the reproductive stage [16] . In the present study, Sargassum during maturation period (September and October) gave highest yield of fucoidan and P. tetrastromatica collected during January, recorded higher yield.…”
Section: Resultsmentioning
confidence: 99%
“…The variation in the monosaccharide composition of fucoidan from U. pinnatifida and was analysed and reported that sulphated galactofucan varied from 19 to 38 mol. Percent galactose dependent on the maturity stage of algae [16] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dalam akuades kelarutan poli sakarida lebih tinggi dibandingkan dengan asam, hal ini merupakan salah satu penyebab kandungan total polisakarida lebih tinggi pada pengekstrak akuades. Kandungan total gula pada fukoidan dipengaruhi beberapa hal antara lain metode ekstraksi, perbedaan spesies, variasi musim, masa tumbuh/panen, lingkungan tempat tumbuh, dan pelarut (Franck et al, 2004;Sinurat et al, 2015;Skriptsova et al, 2009). …”
Section: Kandungan Total Gulaunclassified
“…Fucoidan is a sulfated polysaccharide (MW: average 20,000) found in the brown seaweed and also various species of brown algae such as mozuku, kombu, limu moui, bladderwrack, wakame, and hijiki (variant forms of fucoidan have also been found in animal species, including the sea cucumber). The monosaccharide composition and structure of algal fucoidans appear to depend on algal species, the methods of isolation and purification of polysaccharides harvest from brown seaweeds [11]. Structurally, fucoidan is a heparin-like molecule with a substantial percentage of L-fucose, sulfated ester groups, as well as small proportions of Dxylose, D-galactose, D-mannose, and glucuronic acid [12].…”
Section: Structure and Composition Of Fucoidanmentioning
confidence: 99%